Characterization of Eigenvalues in Spectral Gap for Singular Differential Operators. (26th September 2012) - Zheng, Zhaowen; Zhang, Wenju
Abstract : The spectral properties for n order differential operators are considered. When given a spectral gap ( a, b ) of the minimal operator T 0 with deficiency index r, arbitrary m points β i   ( i = 1, 2, …, m ) in ( a, b ), and a positive integer function p such that ∑ i = 1 m p ( β i ) ≤ r, T 0 has a self-adjoint extension T ̃ such that each β i   ( i = 1, 2, …, m ) is an eigenvalue of T ̃ with multiplicity at least p ( β i ) .